2021
DOI: 10.9734/ajahr/2021/v8i330116
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Coffee Marketing among Smallholder Coffee Farmers in Kogi State, Nigeria

Abstract: The study assessed the determinants of coffee production and marketing on farmers’ farms in Kogi State. Two Local Government Areas (Ijumu and Kabba-Bunu Local Government Areas) were purposively sampled. These areas are known for the production and marketing of coffee. A total sample of eighty-four respondents was randomly selected from the two Local Government Areas. Structured interview schedules were used for data collection from respondents. The data collected were analyzed using inferential statistics anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Strategic management for the coffee industry must involve the ability to identify risks early and deal with them successfully. [99] This research presents the methodology and findings of a study looking at the incidence of risk factors and risk management practices in primary agricultural output. It places emphasis on the distinctive features of the danger.…”
Section: Research Agendamentioning
confidence: 99%
“…Strategic management for the coffee industry must involve the ability to identify risks early and deal with them successfully. [99] This research presents the methodology and findings of a study looking at the incidence of risk factors and risk management practices in primary agricultural output. It places emphasis on the distinctive features of the danger.…”
Section: Research Agendamentioning
confidence: 99%
“…Education of the producers, farm size, coffee variety, and experience were all critical factors. While conducting a similar study to Akinpelu et al (2021), Idrisu et al (2012) reported that coffee is grown by 25 to 30 million small-holder producers in the tropics. The authors used a qualitative approach to discuss the unique challenges to coffee production in Nigeria, such as the abolition of the marketing board, a lack of an appropriate quality control system, adulterated coffee beans, a poor information system for the dissemination of coffee technology, a lack of incentives, and a lack of farm inputs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coffee (Coffee arabica and Robusta coffee) is a popular beverage and a significant source of income for actors along the coffee value chain in Nigeria, as well as a valuable cash crop for enhanced export earnings (Akinpelu et al, 2021;Alli et al, 2021;Mohammed et al, 2013;ICC, 2015;Krishnan, 2017). The coffee tree is a perennial woody tree crop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of coffee supply chain is important for coffee farmers because of the large number of livelihood dependencies, the large number of farmers are involved in coffee farming and lack of incentives for farmers [38]. So, farmers who have access to market information will be able to sell their crops for more profit [39,40]. According to Warnaen et al (2020), indicators of farmer empowerment in coffee farming the weakest management is in the ability to market coffee.…”
Section: Introductionmentioning
confidence: 99%